Young's Modulus and Coefficient of Linear Thermal Expansion of ZnO Conductive and Transparent Ultra-Thin Films - Naoki Yamamoto; Hisao Makino; Tetsuya Yamamoto (Advances in Materials Science and Engineering)
A new technique for measuring Young's modulus of an ultra-thin film, with a thickness in the range of about 10 nm, was developed by combining an optical lever technique for measuring the residual stress and X-ray diffraction for measuring the strain in the film. The new technique was applied to analyze the mechanical properties of Ga-doped ZnO (GZO) films, that have become the focus of significant attention as a substitute material for indium-tin-oxide transparent electrodes. Young's modulus of the as-deposited GZO films decreased with thickness; the values for 30 nm and 500 nm thick films were 205 GPa and 117 GPa, respectively. The coefficient of linear thermal expansion of the GZO films was measured using the new technique in combination with in-situ residual stress measurement during heat-cycle testing. GZO films with 30–100 nm thickness had a coefficient of linear thermal expansion in the range of 4.3 × 10−6 – 5.6 × 10−6 °C−1.